Pengembangan Alat Ukur Kepuasan Pernikahan Pasangan Urban - Rumondor, Pingkan C. B. (Bina Nusantara University, 2013)
The current study aims to validate the measure of marital satisfaction among young urban married couples. Marital satisfaction is defined as a individual’s subjective experience toward marriage or components within a marriage. The scale consists of 38 items measuring individual’s satisfaction in communication, division in roles, agreement, openness, intimacy, intimacy in social relationship, sexuality, finance, and spirituality. The results indicate that the instrument was found to be reliable (α= 0.920) and have low correlation with subjective rating of overall marital satisfaction (rs = 0.293, p < 0.05).